Prevalence of metabolic syndrome in mainland china: a meta-analysis of published studies - Ri Li; Wenchen Li; Zhijun Lun; Huiping Zhang; Zhi Sun; Joseph Sam Kanu; Shuang Qiu; Yi Cheng; Yawen Liu (BMC, 2016)
Abstract Background Metabolic syndrome (MS) comprises a set of conditions that are risk factors for cardiovascular diseases and diabetes. Numerous epidemiological studies on MS have been conducted, but there has not been a systematic analysis of the prevalence of MS in the Chinese population. Therefore, the aim of this study was to estimate the pooled prevalence of MS among subjects in Mainland China. Methods We performed a systematic review by searching both English and Chinese literature databases. Random or fixed effects models were used to summarize the prevalence of MS according to statistical tests for heterogeneity. Subgroup, sensitivity, and meta-regression analyses were performed to address heterogeneity. Publication bias was evaluated using Egger's test. Results Thirty-five papers were included in the meta-analysis, with a total population of 226,653 Chinese subjects. Among subjects aged 15 years and older, the pooled prevalence was 24.5 % (95 % CI: 22.0-26.9 %). By sex, the prevalences were 19.2 % (95 % CI: 16.9-21.6 %) in males and 27.0 % (95 % CI: 23.5-30.5 %) in females. The pooled prevalence of MS increased with age (15-39 years: 13.9 %; 40-59 years: 26.4 %; and ≥60 years: 32.4 %). Individuals living in urban areas (24.9 %, 95 % CI: 18.5-31.3 %) were more likely to suffer from MS than those living in rural areas (19.2 %, 95 % CI: 14.8-23.7 %). Hypertension was the most prevalent component of MS in males (52.8 %), while the most prevalent component of MS for females was central obesity (46.1 %). Conclusions Our systematic review suggested a high prevalence of MS among subjects in Mainland China, indicating that MS is a serious public health problem. Therefore, more attention should be paid to the prevention and control of MS.